Sensory dysfunction and traumatic brain injury severity among deployed post-9/11 veterans: a Chronic Effects of Neurotrauma Consortium study. (24th August 2018) - Swan, Alicia A.; Nelson, Jeremy T.; Pogoda, Terri K.; Amuan, Megan E.; Akin, Faith W.; Pugh, Mary Jo
ABSTRACT: Objectives : To describe the prevalence of sensory dysfunction (i.e. auditory, visual, vestibular, chemosensory and multiple sensory problems) and explore associations with traumatic brain injury (TBI) severity and injury mechanism among deployed Post-9/11 Veterans. Methods : This retrospective cohort analysis used Departments of Defense and Veterans Affairs diagnostic codes and administrative data. Results : Among the 570, 248 Veterans in this cohort, almost 23% had at least one diagnosis of sensory dysfunction. In the multinomial regression analysis, the odds of all types of sensory dysfunction were greater among those with any TBI relative to those with no TBI. The odds for auditory or multisensory problems were higher among those that indicated exposure to blast. In particular, exposure to quaternary blast injury (e.g. crush, respiratory and burn injuries) was associated with increased odds for auditory, visual, vestibular and multisensory problems. Conclusions : Sensory problems affect a substantial number of deployed Post-9/11 Veterans and are more common among those with TBI or with exposure to deployment-related blast exposure. Because sensory problems profoundly impact quality of life, their identification and enhanced education and therapy are vital tools to improve prognosis for these relatively young Veterans.